1991
DOI: 10.1152/jappl.1991.70.2.825
|View full text |Cite
|
Sign up to set email alerts
|

Optimal stiffness of series elastic component in a stretch-shorten cycle activity

Abstract: Twelve experienced male weight lifters performed a rebound bench press and a purely concentric bench press lift. Data were obtained pertaining to 1) the benefits to concentric motion derived from a prior stretch and 2) the movement frequency adopted during performance of the stretch-shorten cycle (SSC) portion of the rebound bench press lift. The subjects also performed a series of quasi-static muscular actions in a position specific to the bench press movement. A brief perturbation was applied to the bar whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
111
3
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 0 publications
13
111
3
5
Order By: Relevance
“…It has been suggested that one of the training methods commonly employed by the Greeks to enhance acrobatic, dancing, and athletic abilities was flexibility training (141).…”
Section: Review Of Literature 20 Introductionmentioning
confidence: 99%
“…It has been suggested that one of the training methods commonly employed by the Greeks to enhance acrobatic, dancing, and athletic abilities was flexibility training (141).…”
Section: Review Of Literature 20 Introductionmentioning
confidence: 99%
“…Decay in the magnitude of potentiation has been 99 observed as the transition time between eccentric and concentric contraction increases 100 (33). These mechanisms then are more likely to contribute to the fast SSC which has a 101 faster eccentric velocity and a shorter transition period than the slow SSC (2).…”
mentioning
confidence: 99%
“…T braking is crucial for the performance on exercises using SSC, since the potentiation effect caused by prior muscle stretching on the concentric action is greater with increasing eccentric action speed and decreases the time of transition between sub-phases 20,29 . The peak eccentric action speed during DJ depends on the maximum de-scending speed of the individual's center of mass 16 , and in water, this speed is reduced due to buoyancy and resistance, causing slower eccentric action.…”
Section: Discussionmentioning
confidence: 99%